Interetniczność w folklorze dzieci na pograniczu polsko-czeskim - Marcol, Katarzyna (Studia Etnologiczne i Antropologiczne, 2011)
The study is devoted to oral, anonymous and collective works of Polish children in Cieszyn Silesia, on both sides of the Polish-Czech national borderline. A special emphasis was put on the repertoire functioning in the environment of Polish minority in Zaolzie, in the Czech Republic. Here, I aim at discussing the interethnic specificity of verbal play by Polish children from Zaolzie by means of a comparison with ethnically Polish store of folklore on the Polish side of the borderline in Cieszyn Silesia and with ethnically Czech texts. Verbal works of Polish national minority in the Czech Republic develops under the constant influence of ethnically foreign culture, language, literature and mass media. The analysis of specific genres of child folklore — rhymes — showed that the texts are marked by the interference of two languages and cultures. It is, however, the proportions between the elements borrowed from other culture and the parent one that bring about the ethnic nature. Borrowings, though, are not taken on passively and mechanically, but are modeled according to the principles of one’s own anonymous works. The influences of Czech enrich the Polish-speaking works of children, are adapted to the poetic system in accordance with the principles of one’s own anonymous works. Verbal play, developing in the situation of a direct presence of the sender and receiver, are incredibly precious for maintaining identity of a child living in the multicultural environment. Spontaneous reactions when playing do not only integrate peer environment, but give the sense of security deriving from the belief that the remaining participants of the act of communication have an analogous system of values, represent a similar worldview, and have a similar sense of aesthetics. A spoken word is a symbol of a live and dynamic culture, which realizes the needs of a group in a natural way. In the system of culture shaped in such a way foreign ethnic influences can only enrich it brings about its interethnic specificity.